Viver a vida consumindo: a telenovela como vitrine de uma sociedade de consumo em pleno horário nobre - MARTINS, Viviane Sales (2011)
Starting from the contextualization of a society influenced by media and consumption culture, it's made a qualitative research with the intention of studying how Brazilian soap opera plays an important role in a context in that the media, with prominence of television, rules the discussed themes and influence the behaviors adopted by the public. The methodological basement is on the speech analysis and in images semiotics analysis. When applying this technique in media study, the relevance is pointed out of linking linguistic constructions with the communicational process loaded of ideological constructions. With semiotics analysis, it is considered the symbolic narrative present in analyzed elements of some chapters of Viver a Vida , exhibited by TV Globo, from September 2009 to May 2010. It's got a contemporary cutting of the sample, prioritizing the research concerning an thematic that involves defining subjects of present as: post modernity; the tripod of century XXI society - of consumption, spectacular and media's; the presence of television in context of mass culture's production and the Brazilian soap opera's influence.